Hard as the Rock Itself : Place and Identity in the American Mining Town - Robertson, David, 1966- (Mining the American West., 2006)
As a result of more than two centuries of mining activity, the United States has numerous historic mining districts. Although each is distinctive, they tend to share a common economic history. Mining is the quintessential "boom and bust" industry. Individual mining operations may differ in terms of mineral commodities, richness of deposits, and operating lifespans, but the finite nature of mineral deposits almost always results in the demise of mining-dependent economies. This book studies three such areas.